Self-sensing concrete with nanomaterials - Chen, Z. (2013)
Conductive concrete containing nano carbon black (NCB) and carbon fibre (CF) to enable the self-diagnosis of strain and damage was studied. The effect of NCB and CF on workability, mechanical properties and fractional change in resistance (FCR) in fresh and hardened concrete was analysed. The relationship between the FCR, the strain of initial geometrical neutral axis (IGNA) and the degree of beam damage was established. The results showed that the relationship between the FCR and the IGNA strain can be described by the First Order Exponential Decay function, and that the slope of this function reflects the sensitivity of conductive concrete. Based on the above relationship and damage mechanics theory, internal damage to the concrete is indicated by the relationship between the degree of damage and resistance. This self-sensing of strain in conductive concrete can be applied in monitoring damage to flexible components.